Homo deus [compact disc, unabridged] : a brief history of tomorrow - Harari, Yuval N. (Harper Audio, 2017)
Examines the civilized world's achievements in controlling famine, disease, and war while making provocative predictions about the evolutionary goals of the twenty-first century.